Exercise modification strategies to prevent and train around shoulder pain - Escalante, G. (Strength and Conditioning Journal, 2017)
This article provides a summary of the literature related to shoulder pain in strength athletes. The prevalence of shoulder injuries and types of shoulder injuries sustained will be reviewed. Exercises that may predispose strength athletes to shoulder injuries and suggestions of specific exercise modifications to reduce the risk of injury will be discussed. Finally, preventive strategies to reduce the likelihood of shoulder injuries will be addressed. For a video abstract describing this issue, see video, supplemental digital content 1, http://links.lww.com/scj/a199